2016
DOI: 10.1080/0284186x.2016.1223341
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for trismus in patients receiving radiotherapy

Abstract: Background: Trismus, a restricted mouth opening in head and neck cancer patients may be caused by tumor infiltration in masticatory muscles, radiation-induced fibrosis or scarring after surgery. It may impede oral functioning severely. The aims of our study were to determine: (1) the incidence of trismus at various time points; and (2) the patient, tumor, and treatment characteristics that predict the development of trismus after radiotherapy in head and neck cancer patients using a large database (n ¼ 641). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 20 publications
(26 reference statements)
3
30
2
2
Order By: Relevance
“…This is in line with other studies that have shown an incidence of trismus of approximately one-third of patients undergoing radiotherapy. 3,5,14 The masseter muscle has previously been identified as a critical risk structure for radiation-induced trismus in HNC, and undoubtedly, the clinical findings and patient-reported outcomes in this study support that theory. 15,16 Keeping in mind the high incidence of TMD symptoms prior to radiotherapy in this population, it can be assumed that the etiology of trismus is multifactorial and a result of both ionizing radiation and longstanding biting parafunction and overloading.…”
Section: Clinical Examination Findingssupporting
confidence: 77%
“…This is in line with other studies that have shown an incidence of trismus of approximately one-third of patients undergoing radiotherapy. 3,5,14 The masseter muscle has previously been identified as a critical risk structure for radiation-induced trismus in HNC, and undoubtedly, the clinical findings and patient-reported outcomes in this study support that theory. 15,16 Keeping in mind the high incidence of TMD symptoms prior to radiotherapy in this population, it can be assumed that the etiology of trismus is multifactorial and a result of both ionizing radiation and longstanding biting parafunction and overloading.…”
Section: Clinical Examination Findingssupporting
confidence: 77%
“…In the present study, patients with oral cancer had significantly more severe trismus at 12-month follow-up, which indicates that this subgroup might benefit the most from mouth-opening exercises. It has previously been shown that both oropharyngeal cancer and oral cancer and its treatment predispose patients to trismus, which our study also indicates [5,15,16]. We therefore suggest that consideration should especially be given to patients with the greatest needs, i.e.…”
Section: Discussionsupporting
confidence: 56%
“…The incidence has been reported to be as high as 79% [1] while a number of studies indicate an incidence between 38% and 52% [2][3][4] where the majority of patients have received 3D conformal radiotherapy (3DCRT). Trismus severity seems to peak at 6 months after treatment and becomes somewhat lower at 12 months after treatment [3,5]. Newer treatment modalities, in particular intensity modulated radiotherapy (IMRT) are reported to have lower risk for trismus development [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of trismus primarily depends on tumor site and size, being the highest in patients with tumors close to the mastication apparatus, i.e. parotid lesions, nasopharyngeal and lateralized oropharyngeal or posterior oral cavity primaries [162164]. The wide prevalence range reported in the literature reflects the differences in the studied populations and, consequently, the dose burden across the studies.…”
Section: Trismusmentioning
confidence: 99%